THU0503 Hip Bone Marrow Lesions in Asymptomatic and Osteoarthritic Adults: Prevalence, Risk Factors and Significance. (23rd January 2014) - Dawson, L.; Wang, Y.; Wluka, A.; Bennell, K.; Cicuttini, F.
Abstract : Background: Bone marrow lesions (BMLs) at the knee have an important role in the pathogenesis of osteoarthritis (OA), being associated with increased pain, accelerated cartilage loss, and increased risk of total knee replacement. However, data is limited for the role of BMLs at the hip. Objectives: The aim of this study was to determine the prevalence and associations of BMLs at the hip in an asymptomatic and an osteoarthritic population. Methods: 142 asymptomatic and 19 participants with hip OA were recruited from existing cohorts. Hip magnetic resonance imaging was performed and used to assess femoral head BMLs, cartilage volume and bone area. Results: The demographic characteristics of the asymptomatic versus the OA population were as follows: age 66.8 +/- 7.4 vs. 59.5 +/- 7.6 years (p<0.001), female 55.6% vs. 57.9% (p=0.85), body mass index 27.6 +/- 4.8 vs. 27.2.+/-.4.8 kg/m 2 (p=0.73). The prevalence of BMLs was 17.6% in the asymptomatic population and 63.2% in the OA population (p<0.001). BMLs were strongly associated with OA after adjusting for age, gender and body mass index (odds ratio 5.32, 95% CI 1.78, 15.9, p=0.003). BMLs were associated with lower femoral head cartilage volume in the whole population (regression coefficient -245.7 mm 3, 95% CI -455.5, -36.0, p=0.02). In the OA population, BMLs were also associated with lower femoral head cartilage volume (regression coefficient -426.6 mm 3, 95% CI -855.2, 2.14, p=0.05) after adjusting for age, gender, body mass index, femoral head bone area and hip OA (for analysis of the total population). Conclusions: Femoral head BMLs are common in those with OA, but are also present in asymptomatic individuals with no clinical hip OA. They are associated with reduced hip cartilage volume. These findings suggest that BMLs at the hip may provide a novel target for the treatment and prevention of hip OA. Disclosure of Interest: None Declared